2016
DOI: 10.1007/s00213-016-4364-0
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, longitudinal study of platelet serotonin and plasma brain-derived neurotrophic factor concentrations in major depression: effects of vortioxetine treatment

Abstract: Conflict of interestThe authors declare no conflicts of interest in relation to the current study, and in general. Abstract Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 52 publications
4
24
2
1
Order By: Relevance
“…139 In patients with major depressive disorder, lower basal plasma BDNF levels have been described consistently, and chronic antidepressant treatment was associated with increased plasma BDNF levels in accordance with clinical improvement. [140][141][142] A post-mortem analysis also found an AD-mediated increase of BDNF levels in multiple brain regions. 143 In non-responders, BDNF levels remained significantly lower.…”
Section: Therapeutic Relevance Of Bdnf Signallingmentioning
confidence: 86%
“…139 In patients with major depressive disorder, lower basal plasma BDNF levels have been described consistently, and chronic antidepressant treatment was associated with increased plasma BDNF levels in accordance with clinical improvement. [140][141][142] A post-mortem analysis also found an AD-mediated increase of BDNF levels in multiple brain regions. 143 In non-responders, BDNF levels remained significantly lower.…”
Section: Therapeutic Relevance Of Bdnf Signallingmentioning
confidence: 86%
“…First, the CUMS procedure in our study may not be strong enough to change the expression of the t5-HT 1A receptor in the hippocampus of tested mice. Second, the 5-HT level decrease in the hippocampus may be a consequence of other receptors' interplay or signaling pathways like the brain derived neurotrophic factor (BDNF), since several studies suggested that 5-HT can stimulate the BDNF gene or protein expression in depressive patients (14) and rodents (15). Further studies are therefore necessary to elucidate this issue.…”
Section: Lmmcs Did Not Change the 5-ht 1a Protein Expression In The Hmentioning
confidence: 99%
“…This compound blocks the SERT as well multiple 5-HT receptors (Sanchez et al, 2015; Sagud et al, 2016). This effect is in line with studies reporting that the combination of antidepressants with atypical antipsychotic drugs (olanzapine, risperidone, quetiapine, aripiprazole, paliperidone, ziprazidone, and amisulpride), can boost the effectiveness of depression treatment (Berman et al, 2007; Thase et al, 2007; Bauer et al, 2009; Han et al, 2013).…”
Section: From the Drugs To Monoaminesmentioning
confidence: 99%